Factors associated with the level of self-efficacy in breastfeeding women from IMSS, Tabasco - Garrido Pérez, Silvia María Guadalupe; Xala Méndez, César Alberto; Domínguez Vega, Guadalupe Montserrat (Horizonte Sanitario, 2023)
Objective: To determine the factors associated with the level of self-efficacy in lactating women from UMF No. 47, IMSS, Tabasco.Material and Methods: Observational, cross-sectional and analytical study, in a sample of 197 lactating women, who met the inclusion criteria. A sociodemographic and obstetric questionnaire designed by the researcher was applied, as well as the breastfeeding self-efficacy scale in its short form (BSES-SF), of 14 items, with Cronbach's alpha of 0.92. The analysis included descriptive statistics, as well as inferential statistics where Pearson's chi-square test was used. The magnitude of association was obtained, with the prevalence risks (2x2 tables), and value of p≤0.05 with Fisher's exact test. The data were processed in the statistical program SPSS 25 and STATA 6.Results: Minimum age 17 and maximum 40, the group of 21-25 years predominated with 31.5% (X2=109.944a, gl=8, p